# How does (x-y)(x^2+xy+y^2)=x^3-y^3 help to prove that derivative of x^(1/3) is 1/(3x^(2/3)) ?

##
Below is the clearer version of the question:

Thank you.

Below is the clearer version of the question:

Thank you.

See below.

By signing up, you agree to our Terms of Service and Privacy Policy

To prove that the derivative of x^(1/3) is 1/(3x^(2/3)), we can use the identity (x-y)(x^2+xy+y^2)=x^3-y^3.

Let's start by rewriting x^(1/3) as x^(1/3) = (x^(1/3))^1.

Now, we can rewrite the expression (x-y)(x^2+xy+y^2) as (x^(1/3) - y^(1/3))((x^(1/3))^2 + (x^(1/3))(y^(1/3)) + (y^(1/3))^2).

Expanding this expression, we get (x^(1/3))^3 - (y^(1/3))^3.

Since (x^(1/3))^3 is equal to x and (y^(1/3))^3 is equal to y, the expression simplifies to x - y.

Now, we can equate this to x^3 - y^3, which gives us x - y = x^3 - y^3.

To find the derivative of x^(1/3), we can differentiate both sides of the equation with respect to x.

The derivative of x - y with respect to x is 1, and the derivative of x^3 - y^3 with respect to x is 3x^2.

Therefore, we have 1 = 3x^2.

Simplifying this equation, we get x^2 = 1/3.

Taking the square root of both sides, we have x = ±√(1/3).

Since we are interested in the positive value of x, we have x = √(1/3).

Substituting this value back into the original expression x^(1/3), we get (√(1/3))^(1/3) = 1/(3√(1/3)).

Simplifying further, we have 1/(3√(1/3)) = 1/(3(1/√3)) = 1/(3/√3) = 1/(3/√3) * (√3/√3) = 1/(3√3/3) = 1/(√3) = √3/3.

Therefore, the derivative of x^(1/3) is 1/(3x^(2/3)).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you find the instantaneous rate of change of #f(x)=4x^2+4x−3# when #x=4#?
- Using the limit definition, how do you differentiate #f(x)=−2/(x + 1)#?
- How do you write the equation of the tangent line to the graph of #y=ln(x^2+e)# at x=0?
- How do you find the average rate of change of #y=sqrtx# over [0,2]?
- How does Leibniz notation work?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7